C1GALT1, Negatively Regulated by miR-181d-5p, Promotes Tumor Progression via Upregulating RAC1 in Lung Adenocarcinoma - Dong, Xiaoxia; Liu, Yongyu; Deng, Xinzhou; Shao, Jun; Tian, Shuangyue; Chen, Shuang; Huang, Rongxin; Lin, Ziao; Chen, Chunli; Shen, Li (Frontiers in Cell and Developmental Biology, 2021)
Glycosyltransferases are frequently dysregulated in lung cancer. Core 1 β 1, 3-galactosyltransferase 1 (C1GALT1), an enzyme highly expressed in various cancers, is correlated with tumor initiation and development. However, the role of C1GALT1 in lung cancer remains poorly understood. In this study, through bioinformatic analysis and clinical validation, we first discovered that C1GALT1 expression was upregulated in lung adenocarcinoma (LUAD) tissues and was closely related to poor prognosis in patients with LUAD. Gain- and loss-of-function experiments showed that C1GALT1 promoted LUAD cell proliferation, migration, and invasion in vitro, as well as tumor formation in vivo. Further investigation demonstrated that RAC1 expression was positively regulated by C1GALT1 in LUAD, whereas silencing Rac1 could reverse C1GALT1-induced tumor growth and metastasis. Moreover, miR-181d-5p was identified as a negative regulator for C1GALT1 in LUAD. As expected, the inhibitory effects of miR-181d-5p on LUAD cell proliferation, migration, and invasion were counteracted by restoration of C1GALT1. In summary, our results highlight the importance of the miR-181d-5p/C1GALT1/RAC1 regulatory axis during LUAD progression. Thus, C1GALT1 may serve as a potential therapeutic target for LUAD.